A Note on Solutions of Linear Systems. (1st August 2013) - Malešević, Branko; Jovović, Ivana; Makragić, Milica; Radičić, Biljana
Abstract : We will consider Rohde's general form of 1 -inverse of a matrix A . The necessary and sufficient condition for consistency of a linear system A x = c will be represented. We will also be concerned with the minimal number of free parameters in Penrose's formula x = A ( 1 ) c + ( I - A ( 1 ) A ) y for obtaining the general solution of the linear system. These results will be applied for finding the general solution of various homogenous and nonhomogenous linear systems as well as for different types of matrix equations.